Breaking down the cellular responses to type I interferon neurotoxicity in the brain - Viengkhou, Barney; Hofer, Markus J. (Frontiers in Immunology, 2023)
Since their original discovery, type I interferons (IFN-Is) have been closely associated with antiviral immune responses. However, their biological functions go far beyond this role, with balanced IFN-I activity being critical to maintain cellular and tissue homeostasis. Recent findings have uncovered a darker side of IFN-Is whereby chronically elevated levels induce devastating neuroinflammatory and neurodegenerative pathologies. The underlying causes of these ‘interferonopathies’ are diverse and include monogenetic syndromes, autoimmune disorders, as well as chronic infections. The prominent involvement of the CNS in these disorders indicates a particular susceptibility of brain cells to IFN-I toxicity. Here we will discuss the current knowledge of how IFN-Is mediate neurotoxicity in the brain by analyzing the cell-type specific responses to IFN-Is in the CNS, and secondly, by exploring the spectrum of neurological disorders arising from increased IFN-Is. Understanding the nature of IFN-I neurotoxicity is a crucial and fundamental step towards development of new therapeutic strategies for interferonopathies.